Pseudo-stable Models for Logic Programs - Felea, Victor (INFOCOMP Journal of Computer Science, 2006)
For a general logic program, a set of n + 1 logic values is considered and an undened value denoted u. Partial multi-valued interpretations are also dened. A general logic program P may contain the constants that are dened for every logic value. A pseudo-negation denoted eh is dened for every integer h, where 0 h < n. A partial ordering denoted h is dened between multi-valued interpretations. Using an operator dened for a program P, a multi-valued pseudo-stable semantics for the program P is introduced. The pseudo-stable models which satisfy certain properties are minimal elements of the set of all models for the program P having those properties. The class of pseudo-stable models for a program P contains strictly the class of 3-valued stable models for P.